PENYULUHAN PERSIAPAN UJI KOMPETENSI HUMAS BAGI KEMENTERIAN DAN BUMN - Muhammad Adi Pribadi; Marilyn Alexander; Brindawan Suraj Murti (Jurnal Bakti Masyarakat Indonesia, 2026)
The Community Service Program (PKM) conducted by the Untar Team (Universitas Tarumanagara) at Lembaga Sertifikasi Profesi Public Relations Indonesia (LSPPRI) aims to provide guidance to prospective participants of the Public Relations (PR) competency test regarding the necessary preparations prior to undertaking the examination. This PKM initiative is important to be implemented as part of efforts to support the government in encouraging skilled individuals to obtain professional certification from the Badan Nasional Sertifikasi Profesi (BNSP). The PKM Untar plays a significant role in motivating public relations practitioners to acquire professional certification in the field. The existence of Untar’s PKM provides opportunities for the public to learn about and participate in the professional certification program for Public Relations. The workshop participants consisted of public relations personnel from one of the Ministries and several State-Owned Enterprises (BUMN), who registered themselves to take the PR competency test at LSPPRI. As a Professional Certification Institute (LSP), LSPPRI has received authorization from BNSP to conduct competency tests, issue PR professional certificates, and prepare competency test materials on behalf of BNSP. The Untar PKM Team contributed by providing education on the implementation process of the PR competency test, determining the appropriate scheme, and developing portfolio preparation strategies. The Head of the Untar PKM Team was invited by the leader of LSPPRI to serve as a facilitator due to his competence and experience as an assessor in the field of public relations. One of the challenges faced by LSPPRI was finding experienced speakers for the workshop, as other assessors were unwilling to take on the role, except for the Head of the Untar PKM Team. Another issue was that many prospective participants lacked knowledge and experience regarding the PR competency test, thus requiring guidance during the workshop to increase their chances of obtaining a “Competent” (K) score from the assessors. The workshop was conducted online on August 22, 2025. The methodology applied in the PKM was qualitative, in which the PKM leader delivered the material using PowerPoint via Zoom, employing a symbolic interaction approach. After one hour of presentation, participants were given the opportunity to freely ask questions to the presenter. The prospective assessees who have attended the counseling sessions obtained a Competent score during the competency test. This demonstrates that the activities conducted by the PKM Untar Team were successful in delivering the quality information required by the community. Keywords: Untar, PKM, LSPPRI, PR, Humas ABSTRAK Program PKM (Pengabdian Kepada Masyarakat) yang dilaksanakan oleh Tim Untar (Universitas Tarumanagara) di Lembaga Sertifikasi Profesi Public Relations Indonesia (LSPPRI) bertujuan untuk memberikan penyuluhan kepada calon peserta uji kompetensi PR (Public Relations) terkait persiapan yang perlu dilakukan sebelum mengikuti uji kompetensi. PKM dengan tema ini penting untuk dilaksanakan sebagai bagian dari upaya membantu pemerintah dalam mendorong Masyarakat yang memiliki keterampilan bekerja untuk mendapatkan sertifikat profesi dari Badan Nasional Sertifikasi Profesi (BNSP). Kegiatan PKM Untar menjadi bagian penting mendorong para profesi humas memiliki sertifikat profesi Humas. Keberadaan PKM Untar memberikan kesempatan pada Masyarakat untuk mengetahui dan mengikuti program sertifikat profesi Humas. Para peserta workshop adalah personil humas dari salah satu Kementerian dan beberapa BUMN (Badan Usaha Milik Negara), yang mendaftarkan diri mereka untuk mengikuti uji kompetensi PR di LSPPRI. Sebagai LSP (Lembaga Sertifikasi Profesi), LSPPRI mendapatkan ijin dari BNSP (Badan Nasional Sertifkasi Profesi) untuk menyelenggarakan uji kompetensi, membuat sertifikat profesi PR dan membuat materi uji kompetensi atas nama BNSP. Tim PKM Untar berperan memberikan edukasi terkait proses pelaksanaan uji kompetensi PR, menentukan skema yang tepat, dan strategi penyusunan portofolio. Ketua Tim PKM Untar mendapatkan undangan dari pimpinan dari LSPPRI untuk menjadi penyuluh karena memiliki kompetensi dan pengalaman sebagai asesor di bidang humas. Permasalahan LSPPRI adalah mencari pembicara yang berpengalaman dalam workshop karena asesor lain tidak bersedia untuk jadi pembicara, kecuali ketua tim PKM Untar. Permasalahan lainnya adalah para calon peserta tidak memiliki pengetahuan dan pengalaman dalam uji kompetensi PR sehingga mereka perlu dibimbing dalam workshop, agar mereka memiliki kesempatan yang besar dalam memperoleh nilai K (Kompeten) dari asesor. Pelaksanaan workshop dilakukan secara daring, pada tanggal 22 Agustus 2025. Metodologi pelaksanaan PKM adalah dengan pendekata kualitatif dimana ketua PKM menyampaikan materi menggunakan ppt melalui media zoom dengan pendekatan interaksi simbolik. Setelah satu jam presentasi, para peserta diberikan keleluasaan untuk bertanya kepada pemateri. Para calon asesi yang telah mengikuti penyuluhan mendapatkan nilai Kompeten saat mengikuti uji kompetensi. Hal ini menunjukkan bahwa kegiatan Tim PKM Untar sukses dalam memberikan kualitas informasi yang di perlukan Masyarakat. Kata kunci: Untar, PKM, LSPPRI, PR, Humas